Meningkatkan Hasil Belajar Matematika Materi Penjumlahan Pecahan Penyebut Berbeda Melalui Model Pembelajaran Kooperatif Tipe STAD (Student Teams Achievement Divisions ) Pada Kelas Vb MIN 3 Bantul - Atmi, Suwi (Literasi: Jurnal Ilmu Pendidikan, 2019)
Learning using the STAD model is motivated by the low activity and student learning outcomes in mathematics with the subject of the addition of the fraction of the denominator of Bebeda in class VB MIN 3 Bantul. This is the cause because teachers do not use methods that activate students so students can participate in the learning process. Therefore learning is carried out using the STAD model. The class action using the STAD type cooperative learning model is carried out in 2 cycles.               Learning using the STAD model aims to obtain data to determine the effectiveness of the type of STAD cooperative learning model in improving learning achievement and student learning activeness in learning mathematics. Learning using the STAD model is carried out in 2 cycles. Each cycle consists of 2 meetings. The subject of learning using the STAD model is students in class VB MIN 3 Bantul consisting of 10 male students and 7 female students. Learning using the STAD model was carried out in the first semester of the 2018/2019 school year between August and September 2018. The data collection technique used observation sheets and test sheets during action and implementation.               The learning outcomes using the STAD model in the first cycle show that the activity and learning achievement increase is still small in scale. Out of 17 students, 11 students completed their studies and 6 students did not complete their studies. In the second cycle learning achievement increased significantly, from 17 students 17 students completed study. Based on the findings, data analysis and data processing obtained from the evaluation evaluation of each cycle in learning using this STAD model, it can be used as a reference regarding the use of STAD type cooperative learning models in the learning process can improve student learning outcomes in learning Addition of Denominators to Verbal Classes in class VB MIN 3 Bantul. Keywords: activeness, learning achievement, STAD type cooperative learning